2016
DOI: 10.1021/acssuschemeng.6b01477
|View full text |Cite
|
Sign up to set email alerts
|

Simple Milligram-Scale Extraction of Formaldehyde from Wood

Abstract: Lignocellulose naturally contains formaldehyde, and generates much more when heated. A simple quantitation of such biogenic formaldehyde is desirable for the analysis and utilization of lignocellulose. Heretofore, a boiling toluene extraction (the perforator method) was the best known technique to determine biogenic formaldehyde in wood. Described here is a simple milligram-scale water extraction that avoids specimen heating. This method was validated by comparison to a laborious extraction using poly­(allylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…No remarkable effect was observed for FE values at different contents of lignin and different pressing times. The resulting FE could be the biogenic formaldehyde originating from wood, which was in agreement with the published works [ 71 , 72 , 73 , 74 , 75 ]. It is well acknowledged that wood contains biogenic formaldehyde from lignin.…”
Section: Resultssupporting
confidence: 91%
“…No remarkable effect was observed for FE values at different contents of lignin and different pressing times. The resulting FE could be the biogenic formaldehyde originating from wood, which was in agreement with the published works [ 71 , 72 , 73 , 74 , 75 ]. It is well acknowledged that wood contains biogenic formaldehyde from lignin.…”
Section: Resultssupporting
confidence: 91%
“…Saturated specimens were subsequently adjusted to 100% moisture content. Heat treatments were conducted in sealed 50 mL serum bottles for 10 or 60 min . The CH 2 O generated during heating remained sealed in the serum bottle and was determined as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…In the living tree or otherwise, wood contains natural, biogenic formaldehyde (CH 2 O), defined here as having a carbon source in wood; and heating generates much higher levels that vary according to wood moisture content, tissue type, and tree species. Biogenic CH 2 O levels vary dramatically for reasons not understood. For instance, Tasooji et al demonstrated that Pinus radiata generates 2–6 times more CH 2 O than does Liriodendron tulipifera and Pinus virginiana when heated at 200 °C (10 min) .…”
Section: Introductionmentioning
confidence: 99%
“…The formaldehyde content of unextracted samples (about 30 mg) was measured as described. , Note that formaldehyde gaseous emissions were not measured; instead the formaldehyde retained in the processed fiber was measured by water extraction, generally as follows. Specimens were sealed in clean, dry serum bottles (crimped aluminum cap with silicone septa) under dry N 2 .…”
Section: Methodsmentioning
confidence: 99%